Moving Contexts Onto New Roads: Clues From Other Disciplines - Welter, Friederike; Baker, Ted (Entrepreneurship Theory and Practice, 2021)
This article responds to Welter’s (2011) call to pay more attention to the diversity of entrepreneurship in theorizing contexts by examining how places come to be understood as entrepreneurial. We draw briefly and selectively on ideas from a quirky set of disciplines, looking at how topics such as narratives and language, memories of the past, built environments, and constellations of power among groups of people interact to shape the emergence and decline of “everyday entrepreneurship places.” Our discussion illustrates some useful cues our research might draw on to challenge and improve theoretical understanding of place in entrepreneurship.